Family visits among nursing home residents during the COVID-19 pandemic: a cross-sectional study - Shoko Kasugai; Shota Hamada; Kotomi Sakai; Nobuo Sakata (BMC Geriatrics)
Abstract Background Loneliness is common among nursing home residents, with decreased social connectedness being linked to an increased risk of mortality. During the COVID-19 pandemic, new modalities for family visits, such as videoconferencing, became available in addition to in-person visits, potentially helping to reduce loneliness. This study aimed to characterize family visits among nursing home residents during the COVID-19 pandemic and investigate their associated factors. Methods Data on the visits, including their modalities, were retrospectively collected from facility records for residents of 4 nursing homes over a 3-month period from 2020 to 2022. The types of visits included in-person visits through acrylic boards or windows and video calls. We evaluated the association between resident characteristics and whether they received any visits, regardless of the modality of visit, using a multivariable logistic regression model. Results The study included 564 participants (mean age, 84.9 years; female, 70.0%); among them, 33.2% were visited, 72.2% of which had video calls. Participants who used video calls (1.1 ± 0.9 times per month) had significantly higher frequencies of visits than those with in-person visits only (0.6 ± 0.5 times) (p < 0.001). Most visitors used video calls, although older visitors were less likely to use video calls than younger visitors (60.0% vs. 80.7%, p = 0.021). Compared to residents who stayed for less than 1 year, those staying 1–1.9 years were more likely to receive family visits (adjusted odds ratios [aOR] = 2.18, 95% confidence intervals [CI] = 1.38–3.44, p = 0.001), while those staying 2 years or longer were less likely to receive such visits (aOR = 0.53, 95% CI = 0.31–0.91, p = 0.021). None of the other variables, including dementia diagnosis, age, sex, and Barthel Index score, were shown to be associated with family visits. Conclusion This study suggests that video calls were widely used for family visits among residents and visitors of nursing homes during the COVID-19 pandemic. For residents with no or infrequent family visits, such as those with shorter or longer lengths of stay, it may be necessary to encourage family engagement and actively incorporate alternative approaches to promote social engagement.